PELATIHAN PEMBUATAN PAVING BLOCK DARI SAMPAH PLASTIK KE JASA KEBERSIHAN KAMPUS - Maria Ulfah; Burmawi Burmawi; Arnita Arnita; Inna Kholidasari; Yusra Yusra (Jurnal Media Pengabdian Kepada Masyarakat, 2022)
ABSTRACT Training on making paving blocks from plastic waste (colored and or clear bags) for cleaning services of campus 3 Universitas Bung has been conducted. The Community Service (PKM) aims to transfer knowledge and skills in the manufacture of paving blocks which have a higher selling value than plastic bag waste. The long-term goal of this program is to support the Padang City Government program to reduce the amount of waste to the Final Disposal Site and become a community business opportunity to increase sources of income. The methods used in this PKM are: 1) preparation of socialization activities, and 2) counseling and training. The campus cleaning service is enthusiastic about this activity and considers that the training adds to their insight in the utilization of plastic waste into paving blocks, which they never knew about that.